Synthesis of Over-Based Magnesium Stearate Using Magnesium Oxide Nanoparticles and Evaluation as Multifunction Lubricating Oil Additives - Al-Messri, Zainab A. K.; Hussein, Saba Zuhair (Iraqi Journal of Science, 2022)
The use of multifunction additives in the lubricant sector has attracted great interest due to their ability to simultaneously improve and add multiple functions. This work describes the preparation and evaluation of over-based magnesium stearate detergent as a multifunction additive by the reaction of stearic acid with carbon dioxide gas in the presence of magnesium oxide nanoparticles and ammonia. The prepared over-based magnesium stearate was evaluated as a multifunction additive through blending it in various concentrations of 1-5 wt/wt% with sixty stock lubricating oils. The American Society for Testing and Materials (ASTM) and the Institute of Petroleum (IP) were used to determine the total base number (TBN), viscosity index (VI), pour point (PP), rust prevention, copper corrosion inhibition, and oxidation stability. The over-based magnesium stearate detergent gave higher values for TBN and detergency efficiency. The blended oil with one percent of the prepared additive showed more rust, oxidation, and corrosion resistance than the standard antioxidant (hindered phenol HP). The VI values of the blended oils showed that the 5 wt/wt% over-based magnesium stearate, which has approximately the same VI values as the blend with 5% of the standard olefin copolymer (OCP), provides better performance.